Capturing cadets’ self-efficacy to promote safe future of seafarer - Purba, Damayanto; Hasugian, Sereati; Harini, Novita Vindri; Zuhri, Zainullah (Management and Entrepreneurship: Trends of Development, 2020)
Human error that causes accidents is one of the most significant concerns of maritime sectors. In fact, most accidents happen mainly due to human error, therefore good decision making is needed. In facing problem, one of the important skills is self-efficacy. The purpose of the article is to explore ways to improve self-efficacy in order to ensure a safe future for seafarers. Cadets should have great self-efficacy in order to make future seafaring safely (even in unexpected condition). This study reports the cadets’ self-efficacy at Collision Prevention regulations on Sea and Guard Service course. The data was taken quantitatively. 142 cadets of the deck department were asked to respond Generalized Self Efficacy questionnaire (GSE). This investigation points out that cadets’ self-efficacy is greater than the international average of GSE. However, cadets need to develop creative thinking skill in dealing with unexpected condition or someone who opposes in gaining their goal. These findings suggest that self-efficacy should be integrated into classroom learning. For the next research instructional design can be developed to improve self-efficacy skill effectively and efficiently.JEL Classification: J20, J28